ANALISIS HUBUNGAN FUNGSI MANAJERIAL KEPALA RUANGAN DENGAN KUALITAS DOKUMENTASI ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSUD PARIAMAN - Fithriyani Fithriyani; Fatma Sri Wahyuni; Vetty Priscilla (Jurnal Akademika Baiturrahim Jambi, 2017)
Background: The quality of nursing care can be drawn from the documentation of nursing care. Nursing care documentation incomplete can degrade the quality of nursing services because it can’t identify the extent to which the success rate of nursing care given. It becomes of performance of nurses. Nurses in performing their duties are also influenced by the ability of the managerial functions of the head nurse that affects the performance of nurses. Methods: This study aimed to analyze the relationship between the head nurse managerial functions with documentation quality of nursing care in inpatient Pariaman Hospitals . The Study using analiytical descriptive  design with cross sectional approach. Samples were 86 nurses with proportional random technique sampling. The  result research showed that planning function, organizing function, directing function, monitoring function, controlling function  majority is good. Results: The statistical test result correlation between the function of directing the quality of nursing care documentation  (p value = 0.042). Suggestions for head of nursing revised Nursing Care Standards, assessing the performance of nurses regarding documentation of nursing care on a regular basis using an assessment instrument and the implementation of training related to nursing care documentation appropriate standard built by experts and professionals.